The impact of Facebook on Zimbabwean University students: Culture dilution or Pedagogical? - Zimuto, Jilson (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The study sought to establish consumer attitudes towards the effect of one Social Network Site (SNS), Facebook on culture dilution or pedagogical potential among university students. This has been necessitated by a plethora of unique social interactions in this era of technological affordances. Many SNSs are in use: Facebook, MySpace, Cyworld, Bebo, WhatsUp, LinkedIn, ChatOn, Opera Mini, Twitter and other new forms keep on emerging. However, of interest Facebook was used in this study because it is impacting the ways in which university students use the Internet. Technology has mediated communication in countless ways. The values and norms of culture have to be cherished the young generation. In investigating this problem, two hundred (200) students were interviewed at their university campus in Zimbabwe. The sample comprised students from Great Zimbabwe University. The research findings proved that Facebook contributes to the dilution of the Zimbabwean culture. It was also interesting to note that other students see the pedagogical potentials of Facebook.